THE EFFECT OF CANVA-ASSISTED STAD TYPE COOPERATIVE LEARNING MODEL ON PHYSICS LEARNING OUTCOMES ON THE MAIN MATERIAL OF MOMENTUM AND IMPULSE OF GRADE X MIPA STUDENTS IN THE EVEN SEMESTER OF SMA MULIA PRATAMA MEDAN IN THE 2022/2023 ACADEMIC YEAR - Andika (Jurnal Edukasi dan Pembelajaran STEM, 2025)
This study aims to determine the effect of the STAD type cooperative learning model assisted by Canva on physics recognizing consequences in the situation of momentum and impulse material for the sophistication of X MIPA SMA Mulia Pratama Medan Academic Year 2022/2023. The type of research is a quasi-experimental study. The population is Class X MIPA semester 1 SMA Mulia Pratama Medan Academic Year 2022/2023. The research pattern was taken from general sampling, which consists of training, namely the experimental class of 30 students carrying out the STAD version of learning assisted by Canva, and the control class of 30 students carrying out the Direct education (DI) model. Research notes were obtained using a tool in the form of an essay test which includes 10 questions that have been tested beforehand to see the validity of the questions, reliability, stages of the questions and discriminating power. Based on the results of the study for the experimental class, received an average pretest of 50.50 with a trendy deviation of 9.45 and an average post-test rating of 85.07 with a desired deviation of 6.06. For the splendor of manipulation, the average pretest value became 49.57 with a standard deviation of 9.18 and the average posttest value became 79.89 with a popular deviation of 5.48. both trainings have been declared generally disbursed (obtained L0 Fcount statistical test (two-tailed t test) for α = 0.05 and dk 58 obtained tcount < ttable, especially 0.418 < 2.002, this shows that the initial abilities in both classes are the same. Then the two classes were given different treatments and at the end of the learning a post-test was given. From the results of the statistical test of the data (one-tailed t test) obtained tcount> ttable, especially 6.143> 1.671, this final result shows that there is a broad influence of the STAD type cooperative learning model assisted by Canva on physics learning in gaining knowledge about the effects in the problem of calculating the amount of momentum and impulse of class X MIPA students semester I SMA Mulia Pratama Medan 2022/2023 academic year.